2011
DOI: 10.5354/0719-0581.2011.17937
|View full text |Cite
|
Sign up to set email alerts
|

Niveles de ansiedad, depresión y percepción de apoyo social en estudiantes de Odontología de la Universidad de Chile

Abstract: Esta investigación tuvo por objetivos describir las variables ansiedad, depresión y apoyo social percibido en estudiantes de Odontología de la Universidad de Chile en dos momentos del semestre académico; y comprobar si con las exigencias curriculares de esta carrera aumentan sus niveles de ansiedad y depresión. Se aplicaron las escalas Hospital Anxiety and Depression Scale -HADS- (Snaith & Zigmond, 1983) y Duke University Functional Social Support -DUFSS- (Broadhead, De Gruy, Gehlbach & Kaplan, 1988). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…The motives of the students for consulting is in agreement with both the national (Misrachi et al, 2015;Dávila et al, 2011) and international literature (Sofola & Jeboda, 2007;Fonseca et al, 2013;Giri et al, 2014), where the symptoms of the emotional ambit are the most prevalent and studied, associated with the attention to patients and clinical requirements, which could be related to the fact that 11 of 12 students that requested psychological care, to have a reason of consulting about symptoms appeared frequently in Dental School, and the cases who completed the treatment were taking clinical courses at the moment.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The motives of the students for consulting is in agreement with both the national (Misrachi et al, 2015;Dávila et al, 2011) and international literature (Sofola & Jeboda, 2007;Fonseca et al, 2013;Giri et al, 2014), where the symptoms of the emotional ambit are the most prevalent and studied, associated with the attention to patients and clinical requirements, which could be related to the fact that 11 of 12 students that requested psychological care, to have a reason of consulting about symptoms appeared frequently in Dental School, and the cases who completed the treatment were taking clinical courses at the moment.…”
Section: Discussionsupporting
confidence: 61%
“…In relation to psychopathology in university students, Herrera & Rivera (2011) indicated that psychological distress increased with less recreation time, lower socioeconomic level, greater worry about expenses and more hours spent studying. More specifically, a study of dental students of the Universidad de Chile (Dávila et al, 2011) found greater predominance of anxiety symptomology than depression; in the final exam period they found 45.9% prevalence for anxiety and 9.9% for depression. Students of the third and fourth years were those who had the highest levels of anxiety symptomology, which these authors associated with the increase in academic load and the beginning of attention of patients, among others.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The presence of positive relationships between perceived social support and emotional well-being is also consistent with other research establishing that: when students perceive greater social support from family and friends, they report greater satisfaction with life (Marrero and Carballeira, 2010;Kong et al, 2012;Kong and You, 2013;King et al, 2020). There is a consensus that close, deep and meaningful social relationships have a positive effect on subjective well-being and other mental health indices (Dávila Figueras et al, 2011;Feeney and Collins, 2015;Poots and Cassidy, 2020). Additionally, the distinction found in the levels of relationship of perceived social support with types of well-being coincides with another study that establishes that the prediction of the perception of social support can vary depending on the well-being indicator taken into account.…”
Section: Relationship Between the Perception Of Social Support And Emsupporting
confidence: 55%
“…5,[12][13][14][15] Though there are studies in Chile that explored most of these variables, the impact on burnout levels of the separation of the student from his family when studying in another city, course reprobation, or type of funding is lacking. [15][16][17][18][19] Thus, this paper aims to determine the association of burnout with socio-educational variables in a sample of Chilean dental students.…”
Section: Introductionmentioning
confidence: 99%